Análisis y evaluación de la cartera de crédito en la Cooperativa de Ahorro y Crédito Cacpe - Loja sucursal Malacatos en el período 2011 – 2012 - Delgado Bazarán, Marieta Del Rosario (2016)
In the present thesis entitled " ANALYSIS AND EVALUATION OF PORTFOLIO CREDIT COOPERATIVE SAVINGS AND CREDIT CACPE - Loja Malacatos BRANCH IN THE PERIOD 2011 - 2012 " the situation is exposed available to the Loan Portfolio . The overall objective is to analyze and evaluate the Portfolio Credit Cooperative Savings and Credit CACPE - Loja , Branch Malacatos in the period 2011 - 2012 , while specific are: A) Analyze current and past portfolio having the cooperative the period 2011 - . 2012 B ) Identify the financial risk of default and the different portfolios. C ) Set the competitive strategies used in the financial environment in the process of collection . To perform the analysis and evaluation of the credit portfolio , an analytical , descriptive and explanatory study of all portfolios that comprise the Portfolio Credit Union Cooperative Credit Union held CACPE - Branch Malacatos Loja and then plotted for the better understanding and a horizontal category portfolio analysis which identified levels of delinquencies and loans portfolios thereof, then apply delinquency indicators and thus know what the default available to the same . The findings suggest a greater focus on consumer loans to overcome with a 92.71 % the same as financing the purchase of vehicles , level four studies , nice house, home credit classes , and institutional arrangements ; and comparative analysis , which became evident to overcome microenterprise portfolio has increased significantly from year to year with a total of 135.84 % , the consumer does not accrue interest to 94.06 % ; and then we have the supplies to 45.16 %. The procedures were performed both statistical and mathematical allowed the development of delinquency indicators that were applied to the Portfolio Credit , with a gross NPL ratio of 3.43 % for 2012 , this being higher than that of 2011 which was 2.14 % . Thus , we proceed to build an Alternative Proposal in which strategies for the recovery of the portfolio is set presents: objectives, policies , scope and time, the document is intended for personal credit and collections of the cooperative in which responsibilities and functions assigned personnel , acceptable margins for recovery, with boundaries of functions and responsible for recovery of loans, the purpose of the cooperative is considered stronger every day and used to direct its resources to the social benefit. Finally we conclude that consumer loans are those with greater participation in the same 2012 period have a 92.71 % of the total loan portfolio , reflecting the wide acceptance of consumer credit offered by the entity the inhabitants of the parish Malacatos , for which the revision and improvement of the Manual Credit Cooperative is recommended in order to set policies and procedures are applicable according to the needs and development of the entity and the partners , making known the products offered by the cooperative and to diversify the structure of the loan portfolio. Also conduct a thorough and constant monitoring to customers who require and have acquired loans in order to meet your repayment capacity and reduce delinquencies in the portfolio also may promote better management of portfolio, which will optimize resources.